L’image du Japon dans « Ni d’Ève, ni d’Adam » d’Amélie Nothomb. Essai critique - Kowalski, Witold (Studia Romanica Posnaniensia, 2011)
The goal of this paper is to present the place of Japan in "Ni d’Ève, ni d’Adam" of Amélie Nothomb. The paper is focused on the experiences and observations of Nothomb about Japanese mentality, civilisation, culture and the clash of cultures which writer lived through during her stay in Japan. The analysis of her images of this Eastern country leads to show an ambiguous and subjective portrait of Japan, sometimes surprisingly stereotypical, where the admiration for Japan turns easily into a disappointment and the incomprehension of Japanese principles and mentality.